Composition of Mitochondrial DNA 16S Nucleotide of Dwarf Snakehead (Channa gachua Hamilton, 1822) from Keji River, Magelang, Central Java - Warisatul Ilmi; Tuty Arisuryanti (Journal of Tropical Biodiversity and Biotechnology, 2018)
Indonesia has a high marine and freshwater biodiversity including freshwater fish biodiversity. One of freshwater fish which is commonly consumed by Indonesian people is dwarf snakehead (Channa gachua Hamilton, 1822). However, research on genetic characterization, especially the composition of mtDNA 16S nucleotide of dwarf snakehead has poorly understood. Therefore, the aim of this study was to determine the composition of mtDNA 16S nucleotide of dwarf snakehead as a part of genetic characterization of the fish species taken from Keji River, Magelang, Central Java which has not been previously examined. This study analyzed 16S mt-DNA of two samples of dwarf snakehead from Keji River (KTS-01 and KTS-02). In addition, two sequences of Channa gachua with accession number KU986900, KU238074, and HM117234-HM117238 taken from GenBank were used as a comparison. A method used in this research was a PCR method and primers used in this research were 16Sar and 16Sbr. The results revealed that the average of nucleotide composition T, C, A and G of the fish species was 23.04%, 25.13%, 29.06% and 22.77% respectively whereas the average rate of nucleotide composition A+ T and G+ C was 52.10% and 47.90% respectively. The two dwarf snakehead had similar T and C composition but different in A and G composition. In addition, the G+C content in KTS-01 and KTS-02 had the highest frequency compared to other dwarf snakehead taken from GenBank. From this finding it could be assumed that there is genetic variation between the two dwarf snakehead from Keji River which is important genetic data for breeding program of the fish species in the future.